The Effect of Profitability, Liquidity, and Asset Tangibility on Capital Structure in Property and Real Estate Companies Listed on the Indonesia Stock Exchange in 2017-2023 - Salafu Zain Al Hamid; Farida Titik Kristanti (Universitas KH. Abdul Chalim Mojokerto, 2025)
This research investigates the impact of asset tangibility, liquidity, and profitability on the capital structure of property and real estate companies listed on the Indonesia Stock Exchange during the 2017–2023 period. These variables were selected due to their central relevance to financial decision-making under the framework of the pecking order and trade-off theories, and their heightened importance amid economic uncertainty such as the COVID-19 pandemic. Asset tangibility represents collateral capacity, liquidity reflects short-term financial flexibility, and profitability indicates internal financing ability all of which are critical under crisis conditions. Utilizing a quantitative approach, the study applies dynamic panel data analysis through the Generalized Method of Moments (GMM) to estimate the regression model. The sample consists of 294 firm-year observations from 42 purposively selected firms over seven years. Statistical analysis reveals that while the three variables jointly have a significant effect on capital structure, only profitability exerts a significant positive impact individually. In contrast, asset tangibility and liquidity show no significant influence when assessed independently. This study contributes new empirical insights into capital structure determinants in Indonesia’s property sector, especially within the context of emerging market volatility and global disruptions, offering a foundation for future research incorporating additional firm-specific or macroeconomic variables.